A new bicyclic sesquiterpenoid from Merremia yunnanensis. (April 2020) - Yuan, Mingrui; Liu, Bin; Ding, Qian; Zhang, Xuerui; Wei, Di; Mei, Shuangxi; Li, Rongtao; Wan, Jinfu; Li, Qian
Abstract: A new sesquiterpenoid, 1 α, 4 β, 8 β, 9 β -eudesmane-tetrol-1- O - β -D-glucopyranoside (1 ), together with nine known compounds (2 –10 ), were isolated from Merremia yunnanensis . The structures of these compounds were elucidated by spectroscopic methods and compared to data in the literature. All these compounds (1 –10 ) were firstly isolated from this plant, and compounds 3, 5, 7, and 10 were reported from the Merremia genus for the first time. The significance of the chemotaxonomy for these compounds is described herein. Graphical abstract: Ten compounds (1 –10 ) were isolated from Merremia yunnanensis . Compounds 3, 5, 7, 10 from the Merremia genus and compounds 1, 2, 4 from Convolvulaceae family were isolated and reported for the first time. Image 1 Highlights: Ten compounds were firstly isolated from Merremia yunnanensis. Compounds 1, 2, 4 from Convolvulaceae family were isolated and reported for the first time. The significance of chemotaxonomy for these compounds is described.